Tolerability and SCFA production after resistant starch supplementation in humans: a systematic review of randomized controlled studies - Sobh, Mohamad; Montroy, Joshua; Daham, Zeinab; Sibbald, Stephanie; Lalu, Manoj; Stintzi, Alain; Mack, David; Fergusson, Dean A (The American journal of clinical nutrition, 2022)
Resistant starches (RSs) have been advocated as a dietary supplement to address microbiota dysbiosis. They are postulated to act through the production of SCFAs. Their clinical tolerability and effect on SCFA production has not been systematically evaluated. We conducted a systematic review of RS supplementation as an intervention in adults (healthy individuals and persons with medical conditions) participating in randomized controlled trials. The primary outcome was tolerability of RS supplementation, the secondary outcome was SCFA production. MEDLINE, Embase, and the Cochrane Central Register were searched. Articles were screened, and data extracted, independently and in duplicate. A total of 39 trials met eligibility criteria, including a total of 2263 patients. Twenty-seven (69%) studies evaluated the impact of RS supplementation in healthy subjects whereas 12 (31%) studies included individuals with an underlying medical condition (e.g., obesity, prediabetes). Type 2 RS was most frequently investigated (29 studies). Of 12 studies performed in subjects with health conditions, 11 reported on tolerability. All studies showed that RS supplementation was tolerated; 9 of these studies used type 2 RS with doses of 20–40 g/d for >4 wk. Of 27 studies performed in healthy subjects, 20 reported on tolerability. In 14 studies, RS supplementation was tolerated, and the majority used type 2 RS with a dose between 20 and 40 g/d. Twenty-one (78%) studies reporting SCFAs used type 2 RS with a dose of 20–40 g/d for 1–4 wk. In 16 of 23 studies (70%), SCFA production was increased, in 7 studies there was no change in SCFA concentration before and after RS supplementation, and in 1 study SCFA concentration decreased. Available evidence suggests that RS supplementation is tolerated in both healthy subjects and in those with an underlying medical condition. In addition, SCFA production was increased in most of the studies. ▪